DEVELOPMENT OF HYDROSTATIC PRESSURE MATERIAL PROPS AT 8th GRADE OF JUNIOR HIGH SCHOOL - Arina Manasikhana; Nur Hayati (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2022)
This research and development was motivated by educators at the Al Chodidijah Integrated Junior High School which is a new junior high school, which opened in 2017. There is no laboratory room and no complete equipment. So that researchers need to develop teaching aids that are able to demonstrate the concept of hydrostatic pressure material. The purpose of this study is to describe the process of developing learning media as a teaching aid for hydrostatic pressure material and to describe the validity of learning media as a teaching aid for hydrostatic pressure material. This type of research uses the R&D (Research and Development) which was adapted from Sugiyono. Which consists of 7 stages. The results of the development of this teaching aid are 1) the process of developing hydrostatic pressure props, namely liquid pressure and Pascal's law using an R&D model through 5 stages, namely problem identification, data collection, product, validation by experts, and phase I revision, 2) has an average feasibility level of 89.09% with a very valid category.